KEARIFAN LOKAL DALAM NOVEL DAWUK KARYA MAHFUD IKHWAN SERTA RELEVANSINYA DALAM PEMBELAJARAN SASTRA DI SMA - Muhammad Satria Aji; Ani Rakhmawati; Chafit Ulya (Universitas Sebelas Maret, 2019)
This study aims to describe and explain (1) the form of local wisdom in the novel Dawuk by Mahfud Ikhwan; and (2) the relevance of Mahfud Ihkwan's Dawuk novel as a literature learning material in high school. This research is a qualitative descriptive study using a literary anthropology approach. The anthropological approach to literature is used to analyze the form of local wisdom in the novel Dawuk. The sampling technique is done using purposive sampling. Data collection techniques are carried out by content analysis or documents and interviews. The data analysis technique in this study uses an interactive analysis model. The results of this study indicate that: (1) the form of local wisdom in the Dawuk novel includes life tools, livelihoods, social systems, language systems, arts, knowledge systems, and religious systems; and (2) Dawuk's novel by Mahfud Ikhwan is relevant as literature learning material in high school for class XII with basic competencies (KD), among others: (a) interpreting the author's view of life in a novel that is read; and (b) analyze the content and language of the novel. Novel Dawuk is also relevant because it has fulfilled three novel selection criteria, namely language, student psychology, and student cultural background.